Visualisasi Konten Media Sosial terhadap Daya Tarik Wayang - Chandra, Vincent Patrick; Erdiansyah, Rezi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Wayang is a cultural thing that has existed in Indonesia since Hinduism spread throughout the archipelago. However, with the development of the puppet era, many young people have abandoned it because puppets are considered an old-fashioned performance, so there is a need for social content tools to echo this puppet tradition. The aim of this research is to identify the impact of depicting social media content on the attractiveness of traditional culture (research on the preservation of wayang culture among young people). The research method used is a descriptive method with a quantitative approach, where the procedure for collecting information uses questionnaires. The research results prove that 1) the results of the t-experiment testing significance prove that there is a probability number of 0.000 ≤ 0.05. This figure can confirm that